Transformer Condition Control. Advanced and Traditional Technologies - Ushakov specialist in the field of electric power engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences; Mytnikov specialist in the field of energy associate Professor of Tomsk Polytechnic University, candidate of technical Sciences; Lavrinovich specialist in the field of power engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences; Lavrinovich Specialist in the field of electric power engineering Technician of Tomsk Polytechnic University (Pover Systems, 2022)
Electrical power has been the technological foundation of industrial societies for many years. Although the systems designed to provide and apply electrical energy have reached a high degree of maturity, unforeseen problems are constantly encountered, necessitating the design of more efficient and reliable systems based on novel technologies. The book series Power Systems is aimed at providing detailed, accurate and sound technical information about these new developments in electrical power engineering. It includes topics on power generation, storage and transmission as well as electrical machines. The monographs and advanced textbooks in this series address researchers, lecturers, industrial engineers and senior students in electrical engineering.